Handbook of Autism and Pervasive Developmental Disorders, Fourth Edition 2014
DOI: 10.1002/9781118911389.hautc42
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐Based Psychosocial Interventions for Individuals With Autism Spectrum Disorders

Abstract: Evidence‐based practice is a multistep process of incorporating empirical evidence, clinical expertise, and patient values to make clinical decisions. In the United States, there are legal mandates (i.e., No Child Left Behind [Public Law 107‐110], Individuals with Disabilities Education Act [Public Law 108‐446]) requiring the use of scientifically based practices. Insurance companies in the United States are increasingly requiring all treatments that provide reimbursement to be evidence‐based, including covera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 172 publications
0
8
0
Order By: Relevance
“…Participating children were repeatedly exposed to a variety of question types, and the use of a prompting hierarchy that ensured consistent feedback until successful engagement in the target behavior was achieved (VanDerHeyden, Snyder, Smith, Sevin, & Longwell, 2005). These opportunities to engage in complete learning trials increased the opportunities children had to learn, thus increasing the intensity of instruction (Reichow & Barton, 2014). Although the literature on shared reading interventions for students with ASD is small, systematic instructional procedures were effective in other studies (Browder et al, 2007; Mims et al, 2012; Mucchetti, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Participating children were repeatedly exposed to a variety of question types, and the use of a prompting hierarchy that ensured consistent feedback until successful engagement in the target behavior was achieved (VanDerHeyden, Snyder, Smith, Sevin, & Longwell, 2005). These opportunities to engage in complete learning trials increased the opportunities children had to learn, thus increasing the intensity of instruction (Reichow & Barton, 2014). Although the literature on shared reading interventions for students with ASD is small, systematic instructional procedures were effective in other studies (Browder et al, 2007; Mims et al, 2012; Mucchetti, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly accepted that autism is a lifelong condition that cannot be cured (O'Reilly, Cook, & Karim, 2012). However, there are a number of intervention approaches that have been linked with improved symptoms of autism and positive outcomes for children with autism (National Autism Center, 2015;Reichow & Barton, 2014;Rogers & Vismara, 2014). Findings of the present study with respect to treatment of autism showed that majority of participants across all teacher education programs believed that autism is not curable and segregated settings are the best settings to serve children with autism.…”
Section: Discussionmentioning
confidence: 99%
“…This process supports the building of a caregiver behavioral management “toolbox” by: (1) identifying behavioral function to inform strategy choice; (2) decreasing behavioral excess as well as increasing appropriate behaviors; and (3) using positive behavioral supports, such as antecedent management (e.g. use of visual supports), reinforcement, and functional communication as the means to modify behaviors (Reichow & Barton, 2014). Results across two pilot studies and two randomized trials of RUBI demonstrated clinically and statistically significant reductions in child disruptive behavior (within-subject effect size ranged from 0.9 to 2.7; (Aman et al, 2009; Bearss et al, 2013, 2015; Handen et al, 2015).…”
mentioning
confidence: 99%